Search Result Clustering Studies in Turkish - Dural, Burak; Diri, Banu (IEEE, 2013)
Contents of the internet is rapidly growing day by day. To reach the information we search on the internet, we're using internet search engines, which can return millions of search results depends on the query. Finding the information needed on the search results can be a massive problem. Search result clustering is a useful operation to solve this problem. One of the most popular search result clustering algorithm is Suffix Tree Clustering can achieve successful results. In this work, we try to improve Suffix Tree Clustering to get more successful results on clustering Turkish web search results.
Keywords: Suffix tree clustering; search result clustering; document clustering; Engineering; Telecommunications